Tourism image of China in the Belarusian mass media - Jiamei, Song (Journal of the Belarusian State University. Journalism, 2019)
The article is devoted to the study of China's external image in Belarusian mass media on the background of Year of China Tourism in Belarus and deepening tourism cooperation between the two countries. We select materials with a high level of quotation when entering the query «China» in Russian in popular search engines Google.by and Yandex.by, including Wikipedia in Russian, tourist sites and and five popular Belarusian and Russian information resources, such as BelTA, «SB. Belarus Segodnya», «Komsomolskaya Pravda in Belarus», «CityDog.by» and Russian blog «Magazeta» to explore China's tourist image. The article also provides various points of view in the Belarusian press on tourism cooperation between the two countries and analyses the strategy of creating tourist image in the modern mass media.
Keywords: tourist image; the role of mass media; Belarusian mass media; People’s Republic of China in the mass media of Belarus